Cosmetic Literacy through a Creative Natural Product-Based Approach for Adolescents in Tangerang - Yulius Evan Christian; Erna Wulandari; Madeline Keke Tanoto; Josh Naomy Junior; Adlyne Carlina Widarma; Sharon Susanto (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
The use of cosmetics among adolescents has increased significantly alongside the rapid growth of the beauty industry. However, several critical issues, such as illegal cosmetics or the misuse of cosmetic products, raise great concern. Adolescents, a growing population with limited literacy regarding product safety, may pose higher health risks. This community service program aimed to improve high school students’ knowledge of safe cosmetic use through an experiential learning approach. The activity was conducted with 39 students (64% female, 36% male) from SMA Strada Santo Thomas Aquino in Tangerang. The research design is quasi-experimental using methods included a combination of lectures and a workshop on natural-based lip balm formulation. Participants' knowledge was assessed using a pre-test and post-test to evaluate changes before and after the educational intervention. The results showed an increase in the mean score from 78 on the pre-test to 97 on the post-test. Statistical analysis using a paired t-test demonstrated that this improvement was statistically significant (p < 0.05). The proportion of participants in the very good category increased substantially from 7.69% to 76.92%. In addition, the satisfaction survey indicated high participant satisfaction, with more than 70% rating the overall implementation of the program as very good, including the quality of educational delivery, topic relevance, practical applicability, and time allocation. In conclusion, the creative, natural-product-based educational program effectively improved cosmetic literacy among adolescents and achieved a high level of participant satisfaction. This approach may serve as an effective strategy for adolescences education.